Hubungan Dukungan Suami Dengan Kepatuhan Kunjungan Kb Suntik 3 Bulan: Literatur Review - Cornelia Widyadhari Gita Paramesti; Is Susiloningtyas (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to critically examine the relationship between husband’s support and compliance with three-month injectable contraceptive visits using a systematic literature review design. Data were derived from peer-reviewed national and international journals published over the past decade and selected through PRISMA procedures based on relevance, methodological rigor, and explicit reporting of both variables. The synthesis indicates that husband’s support functions as a multidimensional construct comprising emotional, informational, instrumental, and decisional elements that shape adherence behavior. Evidence suggests that such support not only reinforces women’s motivation but also interacts with socio-cultural environments and health system structures influencing continuity of contraceptive use. Differences across studies reveal that effectiveness is mediated by communication quality, gender norms, and service accessibility. Strengthening male engagement through integrated reproductive health strategies is therefore essential to improve continuity of care and optimize family planning program outcomes.